2015
DOI: 10.5539/jas.v7n5p195
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Plant Leaf Extract against Colletotrichum gloeosporioides (Penz) Sac. Causing Post-Harvest Disease of Papaya

Abstract: The antifungal activity of selected weed and other plants leaf extract prepared in distilled water and ethanol were tested against anthracnose, the post-harvest disease of papaya (Carica papaya L.) caused by Colletotrichum gloeosporioides. The result from the experiment proved that ethanol leaf extract of weed plant, Lantana camara L.possess significant fungicidal effect on the radial growth of C. gloeosporioides followed by lemon and avocado leaf extract while Mikania micrantha Kunth, Sphagneticola trilobata … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Thus, L. camara extracts could serve as an alternative means of post-harvest mango anthracnose disease management [103]. Ethanol leaf extract of L. camara possessed significant fungicidal effect on the radial growth of C. gloeosporioides causing post-harvest disease of papaya [104]. The antifungal activity of ethanolic and petroleum ether extracts of L. camara leaves and flowers were tested in vitro against phytopathogenic fungus S. rolfsii Sacc., using poison food method.…”
Section: Tomato (Lycopersicon Esculentum)mentioning
confidence: 99%
“…Thus, L. camara extracts could serve as an alternative means of post-harvest mango anthracnose disease management [103]. Ethanol leaf extract of L. camara possessed significant fungicidal effect on the radial growth of C. gloeosporioides causing post-harvest disease of papaya [104]. The antifungal activity of ethanolic and petroleum ether extracts of L. camara leaves and flowers were tested in vitro against phytopathogenic fungus S. rolfsii Sacc., using poison food method.…”
Section: Tomato (Lycopersicon Esculentum)mentioning
confidence: 99%
“…Imtiaj et al (2005) reported that Diathane M-45 and Ridomil MZ Gold were effective in controlling conidial germination of C. gloeosporioides, the causal agents of mango at 500~1000 ppm concentrations. Prasad and Anamika (2015) reported that the extracts of L. camara were found to be most effective for the control of the C. gloeosporioides. Imtiaj et al (2005) found that plant extracts such as C. longa was also most effective against C. gloeosporioides the causal agents of anthracnose of mango.…”
Section: Resultsmentioning
confidence: 99%
“…Chowdhury et al (2015) reported that ethanol extract of A. indica showed complete radial growth inhibition of at 10 and 20% concentration whereas T. erecta showed complete growth inhibition at 20% concentrations. Prasad and Anamika (2015) reported that extracts of L. camara were found most effective for the control of the C. gloeosporioides. Imtiaj et al (2005) found that plant extracts such as Curcuma longa, T. erecta and Zingeber officinale were also highly effective against C. gloeosporioides.…”
Section: Methodsmentioning
confidence: 99%